Migrants, Markets, and Mayors : Rising Above the Employment Challenge in Africa’s Secondary Cities – Key Insights - Christiaensen, Luc; Lozano Gracia, Nancy (World Bank, Washington, DC, 2021)
In our rapidly urbanizing world, mayors often see migrants as a burden to their city’s labor market and a threat to its development. Drawing on national household surveys and four secondary city case studies in Africa, this study finds that migrants, being younger, better educated and/or complementary to the resident labor force, usually strengthen the urban labor force. In secondary cities, labor market outcomes for migrants are at least as good as those for residents. Migrants also contribute increasingly less to urban population growth. Secondary cities thus appear well placed to leverage migration. This requires good urban management that develops land and labor markets, prepares for growth and benefits everyone, migrants as well as residents. Migrant specific interventions are warranted when divisions between natives and migrants are deep. Strengthening the financial, technical, and planning capacity of towns to better integrate migrants is part and parcel of the good job’s agenda.